On similarity of convolution Volterra operators in Sobolev spaces - Romashchenko, G. S. (Methods of Functional Analysis and Topology, 2006)
Necessary and sufficient conditions for a convolution Volterra operator to be similar in a Sobolev space to the operator J^α are obtained. A criterion of similarity is obtained as well.